PENGARUH DEBT TO EQUITY DAN CURRENT RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) Periode 2019-2023 - vita vita ni matus sukiyat; Supriadi Supriadi; Lavenia Indanus Pratiwi (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2025)
This research aims to determine how influential Debt To Equity and Current Ratio partially and simultaneously have on Return On Assets in banking companies listed on the Indonesia Stock Exchange (BEI). This research uses a type of quantitative research which is used to examine a population or sample that has been determined by the researcher. In this research, samples were taken using a purposive sampling technique, namely based on predetermined criteria of 15 banking companies on the Indonesia Stock Exchange for the 2019-2023 period. The data analysis method was carried out using panel data regression analysis with Eviews 12. And using the classic assumption test, T test, F test and Coefficient of Determination test. The test results via the t test showed that the first hypothesis in this research was rejected so that Debt To Equity had no effect on Return On Assets. The second hypothesis of this research is rejected, so the Current Ratio has no effect on Return On Assets. Meanwhile, the f test shows that Debt To Equity and Current Ratio together have no influence on return on assets. Keywords: Debt To Equity, Current Ratio and Return On Assets